Absenteísmo na Atenção Primária à Saúde em um município de grande porte: perspectivas da equipe de enfermagem - Miriam Maria Gonçalves Chaves Possa (2021)
Work plays a prominent role in men's and women's lives, as every human activity transforms the environment and produces something new. Nursing is a strategic category for health services. Absenteeism is the non-attendance at the workplace, which can happen due to the professional's decision or incapacity to be present. The absence of nursing workers causes several impacts on health services, as well as on the population's health. The aim of this study was to analyze the phenomenon of absenteeism in the nursing staff working in the Primary Health Care in the Venda Nova Region in Belo Horizonte from 2019 to 2020. This is a case study with a qualitative approach. For data collection, an interview was conducted through an online platform, using a semi-structured script covering data on age, gender, occupation, education, absenteeism in the period 2019 to 2020, and other issues related to work. In the answers to the interviews, professionals pointed out that the following factors contribute to absenteeism; work overload, pressure, salary and social devaluation of the profession, tensions with users due to system failures, lack of ergonomics in the work environment, among others. Data from recorded interviews were transcribed in full and analyzed using Bardin's content analysis technique. The discussion of the results was organized into four thematic categorical groups, namely: Work overload and exhaustion processes in Nursing, Absenteeism of nursing workers, impacts on quality of care and devaluation and lack of recognition of Nursing. The study indicates absenteeism is a reality among nursing professionals who work in Primary Health Care in Venda Nova Region, in the city of Belo Horizonte. This phenomenon is related to individual workers issues, but mainly to the work process in the Health Basic Units and to the organization.